2018
DOI: 10.1002/cpcb.62
|View full text |Cite
|
Sign up to set email alerts
|

An On‐Chip Method for Long‐Term Growth and Real‐Time Imaging of Brain Organoids

Abstract: Brain organoids are an emerging technique for studying human neurodevelopment in vitro, with biomedical implications. However, three‐dimensional tissue culture poses several challenges, including lack of nutrient exchange at the organoid core and limited imaging accessibility of whole organoids. Here we present a method for culturing organoids in a micro‐fabricated device that enables in situ real‐time imaging over weeks with efficient nutrient exchange by diffusion. Our on‐chip approach offers a means for stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This phenomenon has been observed in mathematical models, computer simulations, and swelling gels models [57,58,59,60]. Recently, we have observed folding of human brain organoids cultured in confined microdevices [7,61]. Despite the early onset of gyrification in the organoids, our results indicate that the organoid surface folding is driven by a combination of differential growth and tension at the apical surface.…”
Section: Recapitulation Of In Vivo Neurodevelopmentsupporting
confidence: 64%
See 1 more Smart Citation
“…This phenomenon has been observed in mathematical models, computer simulations, and swelling gels models [57,58,59,60]. Recently, we have observed folding of human brain organoids cultured in confined microdevices [7,61]. Despite the early onset of gyrification in the organoids, our results indicate that the organoid surface folding is driven by a combination of differential growth and tension at the apical surface.…”
Section: Recapitulation Of In Vivo Neurodevelopmentsupporting
confidence: 64%
“…Microfluidic devices have been previously designed for 3D spheroid cultures [123,124]. We have recently developed a microfabricated device to improve organoid culture conditions and enable long-term live-imaging (Figure 3a) [7,61]. The device consisted of a reaction chamber of 150μm height, confined between an imaging compatible coverslip and a semipermeable membrane, coupled to a media reservoir.…”
Section: Bioengineering Challenges and Opportunities In Brain Orgamentioning
confidence: 99%
“…Folding increased the 3D surface area size of the organoids, however, due to folding on the surface, the circularity decreased. Previous studies, using ECM embedding or confining EBs in laminated devices, demonstrated that wrinkling formation is induced and modulated by the mechanical micro-environment of the outer layer cells [ 11 , 65 , 66 ]. We believe our microwell device played a similar role by providing spatial confinement to the growing EBs.…”
Section: Resultsmentioning
confidence: 99%
“…We used early passages of the NIH-approved embryonic stem cell line NIHhESC-10-0079 (WIBR3), which were stably labeled with a fluorescent H2B-mCherry reporter, labeling histones, and a LifeAct-GFP reporter labeling actin, as previously described [6] and maintained in NHSM media [33,34]. Cell transfection was carried out in a NEPA21 electroporation system according to the company's protocol (Nepa Gene, Chiba, Japan).…”
Section: Cell Linesmentioning
confidence: 99%
“…The NHSM media contained DMEM/F12 (21331-020 Gibco, ThermoFisher, Waltham, MA, USA), Albumax I (5gr, 11020-039, Invitrogen, Carlsbad, CA, USA), Pen-strep (5 mL, 03-031-1B, Biological Industries, Beit HaEmek, Israel), L-glutamine (5 mL, 02-022-1B, Biological Industries, Beit HaEmek, Israel), NEAA (5 mL, 01-340-1B, Biological Industries, Beit HaEmek, Israel), KSR (Knockout Serum Replacement, 50 mL, 10828-028, Invitrogen, Carlsbad, CA, USA), human insulin (12.5 µg/mL I-1882, Sigma, St. Louis, MO, USA), Apo-transferrin 100 µg/mL T-1147 Sigma, St. Louis, MO, USA), Progesterone 0.02 µg/mL P8783 Sigma, St. Louis, MO, USA), Putrescine 16 µg/mL P5780, Sigma, St. Louis, MO, USA), Sodium selenite 30 nM S5261 Sigma, St. Louis, MO, USA), 2-mercaptoethanol 50 mM (50 µL, 31350-10 Gibco, ThermoFisher, Waltham, MA, USA), L-ascorbic acid 2-phosphate (Vitamin C, 50 µg/mL, A92902, Sigma, St. Louis, MO, USA), Human LIF (20 ng/mL, Homemade), FGF2 Recombinant human (FGF-basic; 8 ng/mL, 100-18B, Rocky Hill, NJ, USA), TGFB1 (1 ng/mL, 100-21c, Peprotech, Rocky Hill, NJ, USA), IWR1 (5 µM, HY-12238, Medchem Express, Monmouth Junction, NJ, USA), Chir99021 (3 µM, HY-10182, Medchem Express, St. Louis, MO, USA), ERKi (PD0325901, 1 µM, HY-10254, Medchem Express, Monmouth Junction, NJ, USA), p38i (BIRB0796, 2 µM, HY-10320, Medchem Express, USA), JNKi (SP600125, 5 µM, 1496, Tocris, Bristol, UK), BMPi (LDN193189, 0.4 µM, HY-12071A, Medchem Express, Monmouth Junction, NJ, USA) and ROCKi (Y27632, 5 µM, HY-10583, Medchem Express, Monmouth Junction, NJ, USA). The Matrigel-coated plates were prepared as previously described [34]. Briefly, 10 cm tissue-culture plates were coated with 1:100 Matrigel diluted in DMEM/F12 (21331-020 Gibco, ThermoFisher, Waltham, MA, USA) and kept at 37 • C for at least 2 h before use.…”
Section: Human Esc Aggregatesmentioning
confidence: 99%